Intraoperative Proximal Tibia Periprosthetic Fractures in Primary Total Knee Arthroplasty - Damsgaard, Christopher W.; Gad, Bishoy V.; Bono, Olivia J.; Anderson, Marie C.; Brown, Jonathon M.; Bono, James V.; Talmo, Carl T. (The Journal of Knee Surgery, 2020)
Intraoperative fracture of the proximal tibia is a rare complication of total knee arthroplasty (TKA) with few studies available reporting risk factors or prognosis. A review of our prospective joint registry was performed to determine the incidence and associated risk factors of intraoperative tibia fractures during primary TKA; 14,966 TKAs of all manufacturers were performed with 9 intraoperative tibia fractures. All fractures occurred in a single TKA design. There were 8,155 TKAs of this design performed with a fracture incidence of 0.110%. All but one fracture occurred on the medial tibial plateau, and all but one occurred during preparation of the tibia with keel punching. A control group of 75 patients (80 knees) with the same TKA design were randomly selected. Baseplates size 3 or smaller were less likely to experience an intraoperative fracture (odds ratio [OR]: 0.864, 95% confidence interval [CI]: 0.785–0.951), as were knees with a polyethylene insert thickness of 13 mm or larger (OR: 0.882, 95% CI: 0.812–0.957). Fractures were treated with a variety of different methods, but every patient had at least one screw placed and most (67%) had postoperative weight-bearing restrictions. At final follow-up, there were no cases of nonunion, component subsidence, or need for reoperation. Intraoperative tibia fractures are a rare complication of this TKA design at 0.11%. Knees with baseplates of size ≤3 and polyethylene thickness ≥13 mm were less likely to experience intraoperative fracture. These findings may be related to the depth of tibial resection, requiring the use of a thicker polyethylene insert, and a change in the keel width in implants size 4 or larger. No fracture patients required reoperation.
Keywords: intraoperative; proximal tibia; periprosthetic; fracture; total knee arthroplasty